Investigation of phase separation behavior and formation of plasmonic nanocomposites from polypeptide-gold nanorod nanoassemblies - Huang, Huang-Chiao (Langmuir : the ACS journal of surfaces and colloids, 2012)
Genetically engineered elastin-like polypeptides (ELP) can be interfaced with cetyltrimethyl ammonium bromide (CTAB)-stabilized gold nanorods (GNRs) resulting in the formation of stable dispersions (nanoassemblies). Increasing the dispersion temperature beyond the ELP transition temperature results in phase separation and formation of solid-phase ELP-GNR matrices (nanocomposites). Here, we investigated different physicochemical conditions that influence nanocomposite formation from temperature-induced phase separation of ELP-GNR nanoassemblies. The presence of cetyltrimethyl ammonium bromide (CTAB), used to template the formation of gold nanorods, plays a significant role in the phase separation behavior, with high concentrations of the surfactant leading to dramatic enhancements in ELP transition temperature. Nanocomposites could be generated at 37 °C in the presence of low CTAB concentrations (<1.5 mM); higher concentrations of CTAB necessitated higher temperatures (60 °C) due to elevated transition temperatures. The concentration of gold nanorods, however, had minimal influence on the phase separation behavior and nanocomposite formation. Further analysis of the kinetics of nanocomposite formation using a mathematical model indicated that CTAB largely influenced the early event of coacervation of ELP-GNR nanoassemblies leading to nanocomposites, but had minimal effect on nanocomposite maturation, which is a later-stage longer event. Finally, nanocomposites prepared in the presence of low CTAB concentrations demonstrated a superior photothermal response following laser irradiation compared to those generated using higher CTAB concentrations. Our results on understanding the formation of plasmonic/photothermal ELP-GNR nanocomposites have significant implications for tissue engineering, regenerative medicine, and drug delivery